Characterization and physicochemical properties of a novel microencapsulated bio-calcium from Asian sea bass bones - Salinee Phengleng; Wipavadee Sangadkit; Songsak Wattanachaisaereekul; Jiraporn Sirison; Suneerat Ruangsomboon (Food Hydrocolloids for Health, 2025)
• Microencapsulated bio-calcium powders from Asian sea bass bones were successfully produced by spray drying. • The characteristics and physicochemical properties of the powders depended on the type of wall material used. • Encapsulation with maltodextrin, gum arabic, or their combination improved the potential use of bio-calcium in calcium-fortified foods and supplements. Calcium is the most abundant mineral in the human body, yet intake remains insufficient in many populations. Fishbone-derived bio-calcium from Asian sea bass ( Lates calcarifer ), containing approximately 37.5 % calcium (dry weight), offers a cost-effective source. However, its primary form, hydroxyapatite, has low solubility due to high crystallinity, limiting its application in food fortification. This study aimed to enhance the physicochemical properties of bio-calcium (B) powders by encapsulating them with maltodextrin (M), gum arabic (G), and their combination (MG) at 5 %, 10 %, and 15 % (w/v) using spray drying. A 1:4 (w/w) ratio of B to wall materials was applied at 180 °C (inlet) and 60 °C (outlet) temperatures. Powder yields ranged from 25.2 % (15 % BG) to 30.3 % (15 % BM), with no significant differences ( p > 0.05) among treatments. Encapsulated powders had higher lightness (L*) than B. The highest calcium content and encapsulation efficiency were observed in 5 % BG, while BM showed the lowest. Moisture content and water activity remained below 10 % and 0.6 %, respectively. BG had the highest hygroscopicity, while wall concentration had no significant (p > 0.05) impact. Encapsulation improved water solubility index (75.4–86.5 %), especially in BM. Particle sizes ranged from 0.92 µm (10 % BMG) to 2.89 µm (15 % BM), while zeta potentials ranged from -8.71 mV (15 % BM) to -20.90 mV (15 % BMG). Encapsulated powders were more spherical and smoother than B, while BG particles showed aggregation, whereas BMG showed mixed morphologies. These findings suggest that encapsulation enhanced the physicochemical properties of bio-calcium, supporting its potential application in calcium-fortified foods and dietary supplements.
Keywords: Biochemical effects in animals; Microencapsulation and Drying Processes; Protein Hydrolysis and Bioactive Peptides